Low-grade fibromyxoid sarcoma in a child presenting as a popliteal fossa swelling - Suraj Gandhi; Charu Sharma; Pankaj Dwivedi; Neha Sisodiya Shenoy; Hemanshi Shah (Hygeia Press di Corridori Marinella, 2017)
Popliteal fossa masses are rare in paediatric age group. Even rarer are the malignancies of this area. Low-grade fibromyxoid sarcoma (LGFMS) is a distinctive variant of fibrosarcoma. It is a rare tumor with benign histologic appearance but high metastasizing potential. We describe an 11-year-old child with a popliteal fossa mass, which was excised, and histopathological report revealed LGFMS.